THE FORMATION OF KEY COMPETENCIES IN PRESCHOOL CHILDREN BY MEANS OF FOLKLORE - Muzyka, Оlena O.; Laptinova, Daria G. (Educological discourse, 2015)
This article deals with the actual questions of personality development in the preschool age on the basis of competence approach realization. The aim is to explore the possibilities of folklore traditions in the formation of the preschoolers competencies. Experimentally confirmed that the use of proverbs and sayings can serve as a means of psychological support for skills and abilities development of the child in activities. Psychological support should be based on the system of measures aimed at creating favorable conditions for the formation of competence in preschool age.